(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Literature has always served as a powerful tool for social commentary. From ancient epics to contemporary novels, authors have used their craft to critique societal norms, expose injustices, and spark conversations about important issues. This paper explores the multifaceted role of social commentary in literature, examining its various forms, historical development, and impact on society. Social commentary has long been a cornerstone of literature, serving as a powerful tool for authors to reflect the realities of their societies and spark critical discourse. This paper explores the multifaceted role of social commentary in literature, examining its diverse forms (satire, allegory, realism, symbolism), historical development across various eras, and its enduring impact on raising awareness, sparking dialogue, and inspiring social change. The paper also acknowledges the challenges and limitations of social commentary, such as potential biases and limitations of audience reach.